Analysis of Risk Factors Associated with the Incidence of Placenta Accreta at an Indonesian Tertiary Hospital - Aisha Grayli Cahyani; Willy Sandhika; Gatut Hardianto (Folia Medica Indonesiana)
Highlights: 1. The increased incidence of placenta accreta is contributed significantly by parity classification, a history of cesarean section, body mass index, and interbirth interval. 2. The findings of this study can be used as an additional reference in determining the risk of placenta accreta in pregnant women, specifically as an input in screening and antenatal care programs for pregnant women to provide early detection and appropriate management.